Tunable bending stiffness of MoSe2/WSe2 heterobilayers from flexural wrinkling. (18th April 2017) - Guo, Yufeng; Qiu, Jiapeng; Guo, Wanlin
Abstract: Understanding the mechanical behaviors of van der Waals heterogeneous 2D materials is important for their actual applications. Our extensive first-principles calculations and continuum mechanical modeling on the wrinkling of MoSe2 /WSe2 heterobilayers caused by compression reveal that the bending stiffness of MoSe2 /WSe2 wrinkles strongly depend on the wrinkle structures, which first increase and then decrease with increasing the compressive strain. The bending stiffness of MoSe2 /WSe2 wrinkles could be effectively mediated and tuned by adjusting the wrinkle geometry and size. The underlying mechanisms are elucidated by the differences in electronic structures and bonding states at the top, middle and bottom parts of the wrinkles, and the relevance of the changes of bond lengths to flexural deformation. Our results suggest a feasible way to develop flexible devices and nanoelectromechanical systems by utilizing the correlation and coupling between the mechanical and electronic properties in MoSe2 /WSe2 wrinkles.